Oso en un cuadrado - Blackstone, Stella; Harter, Debbie; Meza-Riedewald, Leticia; Blackstone, Stella (Cambridge, MA : Barefoot Books, 2009)
Bear looks for shapes everywhere, such as rectangles at school and stars in the nighttime sky.
"A Barefoot Spanish & English bilingual book"--Cover.
"First published in Great Britain by Barefoot Ltd in 1998 and 2001 and in the United States of America by Barefoot Books Inc in 1998"--Copyright p.
Keywords: Bears -- Juvenile fiction; Osos -- Novela juvenil; Shape -- Juvenile fiction; Stories in rhyme